Frequency of Non-ST-Elevation Myocardial Infarction (NSTEMI) among Patients Presenting with Atypical Presentation: NSTEMI among Patients with Atypical Presentation - Ahmed , Sumair; Ali, Muhammad; Rehman, Adeel Ur; Ahmed, Zuhaib; Shaikh, Salman Ishaque; Sumair, Fiza (Pakistan Journal of Health Sciences, 2023)
Non-ST-Elevation Myocardial Infarction (NSTEMI) occurs when there is a partial or complete blockage of blood flow to the heart muscle. Atypical symptoms may also be more commonly observed in patients with non-obstructive coronary artery disease, which is characterized by the presence of plaque but without significant stenosis. Objective: To find the incidence of Non-ST-Elevation Myocardial Infarction (NSTEMI) among the patients with atypical presentation. It was a cross-sectional study conducted at Tabba Heart Institute, Karachi for the duration of six months from 19th December 2019 to 18th June 2020. Methods: The study was carried out on 257 patients. The average age of patients was 56.33 ± 8.07 years; mean height was measured as 162.89 ± 7.75 cm, mean weight was 72.51 ± 15.26 kg and average BMI of patients was 27.2 8 ± 5.25 kg/m2. In distribution of gender, out of 257 patients, 155 (60.3%) were male while 102 (39.7%) were female Results: Hypertension was noted in 155 (60.3%) patients, diabetes mellitus was documented in 109 (42.4%) patients. Positive family history of premature CAD was found to be in 31(12.1%) while 226 (87.9%) had negative family history. Non-ST elevation myocardial infraction was noted in 77 (30%) patients. Conclusions: As NSTEMI is linked with high chance of mortality and severe medical issues therefore, it was vital to study the underlying risk factors so that the burden of diseases can be lowered and optimization of the management strategies can be made for this already compromised cohort of patient.